Computational models for the structural crashworthiness analysis of a fixed-type offshore platform in collisions with an offshore supply vessel - Mujeeb-Ahmed, M. P.; Ince, Serdar Turgut; Paik, Jeom Kee (ELSEVIER SCI LTD, 2020)
The aim of this paper was to develop practical modelling techniques for the structural crashworthiness analysis in collisions between a fixed-type offshore platform and an offshore supply vessel (OSV). The computational models used nonlinear finite element method involving large deformations (strains) of both vessel and offshore platform, dynamic effects of material (e.g., strain rate and dynamic fracture strain), and the influence of surrounding waters. The applicability of the modelling techniques was demonstrated with an applied example to collisions between an OSV and a jacket-type offshore platform, where a sensitivity analysis was carried out for different collision parameters (e.g., collision velocities and impact locations). It is concluded that the computational models can ultimately be employed for quantitative risk assessment of fixed-type offshore structures collided with an OSV, which requires to perform the structural crashworthiness analysis.
Keywords: Fixed-type offshore structures; Offshore supply vessel; Collisions; Structural crashworthiness; Jacket-type offshore platform; Nonlinear finite element method (NLFEM); Quantitative collision risk assessment and management; PROBABILISTIC APPROACH; NUMERICAL-ANALYSIS; SHIP; DESIGN; STEEL; IMPACT; BOW; Engineering; Mechanics